Antibacterial Activity of Extract and Fraction of Baccaurea macrocarpa Leaf on Escherichia coli and Bacillus cereus - Zamzani, Irfan; Triadisti, Nita (Universitas Muhammadiyah Surakarta, 2019)
Purpose: The purpose of the present study is to investigate antibacterial activity of extract and fraction of Baccaurea macrocarpa leaf, and to identify secondary metabolite contents of the best activity.Methodology: Baccaurea macrocarpa leaf was extracted by using maceration method with the use of methanol solvent. The extract was then fractionated by adopting n-hexane and ethyl acetate by using liquid-liquid extraction. Antibacterial activity assay was performed by using inhibition zone assay particularly Disc Diffusion Susceptibility method from methanol extract and fraction extract of ethyl acetate and n-hexane. Phytochemical screening as the best activity was performed by using by adopting Thin Layer Chromatography (TLC). Result: Antibacterial activity was identified in the ethyl acetate extract of Baccaurea macrocarpa leaf. In addition, secondary metabolites with the best activity such as alkaloid, anthraquinone, flavonoid, and tannin were identifiable in the fraction extract of ethyl acetate of Baccaurea macrocarpa.